An overview of direct sales in the business market of Bangladesh: a study on Grameenphone Ltd. - Ahmed, Taukir (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.